Characteristics and survival of patients with primary biliary cholangitis and hepatocellular carcinoma. Issue 9 (September 2022) - Giannini, Edoardo G.; Pieri, Giulia; Labanca, Sara; Plaz Torres, Maria Corina; Gasbarrini, Antonio; Biasini, Elisabetta; Campani, Claudia; Cazzagon, Nora; Foschi, Francesco Giuseppe; Mega, Andrea; Masotto, Alberto; Raimondo, Giovanni; et al.
Abstract: Background: Comprehensive and contemporary data pertaining large populations of patients with Primary Biliary Cholangitis (PBC) and hepatocellular carcinoma (HCC) are missing. Aim: To describe main characteristics and outcome of PBC patients with HCC diagnosed in the new millennium. Methods: Analysing the Italian Liver Cancer registry we identified 80 PBC patients with HCC diagnosed after the year 2000, and described their clinical characteristics, access to treatment and survival. Results: Median age of patients was 71 years and 50.0% were males. Cirrhosis was present in 86.3% of patients, being well-compensated in 58.0%. Median HCC diameter was smaller in patients under surveillance (2.6 vs 4.0 cm, P = 0.007). Curative treatment, feasible in 50.0% of patients, was associated with improved survival compared to palliative and supportive care (42 vs 33 vs 6 months, P <0.0001). Surveillance was associated with a non-significant improved survival (36 vs 23 months), likely due to similar rate of curative treatment in patients under (51.4%) and outside surveillance (42.6%). Conclusions: PBC patients with HCC are often elderly males with well-preserved liver function. Feasibility of curative treatment is high and associated with improved prognosis. Description of these patients may help focus surveillance to identify earlier tumours, increase their curability, and improve prognosis.